A Female Color Ornament Honestly Signals Fecundity - Lüdtke, Deike U.; Foerster, Katharina (Frontiers in Ecology and Evolution, 2019)
In many species, particularly in ectothermic vertebrates, not only males but also females show bright body colorations. In Alpine newts, Ichthyosaura alpestris, both sexes have colorful orange bellies. This coloration varies in redness (yellowish to dark orange) among individuals, and previous work has shown that courting males preferred females with more orange bellies. Because males in this species are likely to be limited in their mating capacity, selection would favor this preference if this coloration honestly signals female quality. In this study, we investigated whether female belly coloration can predict individual fecundity in which case males might have the chance to fertilize more eggs when they choose to mate with a more ornamented female. We found that more orange females were more fertile than less orange ones. Additionally, we saw that more ornamented females could lay their eggs faster, which means that they ceased egg laying at a similar time as less ornamented females despite the greater number of eggs. This suggests that female color can convey quality advantages in a species with no sex-role reversal much in the same way as male colors can, making female ornaments subject to sexual selection acting directly on them.